Scaling and dimensional methods to incorporate knock and flammability limits in models of high-efficiency gasoline and ethanol engines. (February 2015) - Lewis, Anne; Ortiz-Soto, Elliott; Lavoie, George; Assanis, Dennis N
Recent work has shown the utility of using simplified models with prescribed burn rates to assess the potential of advanced combustion strategies to increase engine efficiency. However, this approach can be improved by incorporating knock and flammability limits. This work incorporates such limits using a combination of simplified conceptual models that are based on theoretical understanding of knock and flame phenomenon and calibration with experimental results. Using this method, the ideal (unconstrained) and feasible (constrained by knock and flammability) potential of a high efficiency gasoline and E85 engine are compared against a baseline naturally aspirated gasoline engine. Turbocharging, dilution with EGR, and higher compression ratios are used to increase the efficiency potential of the high efficiency gasoline and E85 engines. Results demonstrate the benefit of using this simplified approach in modeling high efficiency engines: the high efficiency gasoline engine is most limited by knock while the E85 engine is limited much less; also increased EGR can be used for the E85 engine due to the higher flame speeds of ethanol. Fuel economy maps are created for each engine/fuel strategy and evaluated in a vehicle model to obtain fuel economy results. Results comparing feasible engines show that peak brake thermal efficiency (BTE) is increased by 11.4% for the high efficiency gasoline engine and 17.8% for the E85 engine, as compared to the baseline gasoline engine. Projected vehicle fuel economy (energy equivalent) improvements are 30.1% for the high efficiency gasoline, and 40.9% for the E85 engine relative to baseline.